Stages and elements affecting development of low carbon parks in Malaysia: an expert review - Badrul Hisham, Fara Diba; Shahidan, Mohd Fairuz; Ja'afar, Mohamad Fakri Zaky (Faculty of Design & Architecture, Universiti Putra Malaysia, 2018)
The purpose of this paper is to explore carbon performance at Malaysia Parks. This article aims to identify stages and elements that contribute carbon emission at parks based on expert review. The stages and elements were identified through document review process and experts validation. At the end of these phases, a list of carbon contributor at parks is proposed. Based on findings, (3) three stages (construction, operation and maintenance) and (24) twenty-four elements have been identified from the literature. Afterwards, data will be collected from two Landscape Architects (LA), two Subject Matter Experts (SME), and two Contractor Experts (CE). Fleiss kappa analysis was used to measure the percent agreement to determine interrater reliability. In order to measure the percent agreement among the data collectors, a matrix table has been created. The finding from this study it is reveals that parks also contributes carbon to environment. The findings of the study substantially highlighted that all experts agreed with the stages and elements that contribute carbon to the parks. The main contribution of this paper is to highlight stages and elements needed to be taken into account when creating a sustainability parks in Malaysia.